2004
DOI: 10.1021/ma048487+
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis by RAFT of Amphiphilic Block and Comblike Cationic Copolymers and Their Use in Emulsion Polymerization for the Electrosteric Stabilization of Latexes

Abstract: A series of diblock and comblike copolymers based on styrene and 4-vinylbenzyl chloride were synthesized by reversible addition fragmentation transfer (RAFT) using benzyl dithiobenzoate as a control agent. After quaternization of the well-defined hydrophobic precursors with triethylamine, the micellar aggregates, formed by the cationic amphiphilic diblock copolymer when dissolved in water, were investigated by static and dynamic light scattering. The spherical shape of the micelles was established in salted wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 54 publications
0
57
0
Order By: Relevance
“…RAFT operates on the principle of a rapid and reversible transfer of the growing radical to thiocarbonylthio compounds [34], as illustrated in Scheme 6. The thiocarbonylthio group(s) is retained in the polymer which can be reactivated for use as precursors to produce block polymers, star polymers or polymers with more complex architectures [35].…”
Section: Reversible Addition-fragmentation Transfer (Raft) Polymerizamentioning
confidence: 99%
See 4 more Smart Citations
“…RAFT operates on the principle of a rapid and reversible transfer of the growing radical to thiocarbonylthio compounds [34], as illustrated in Scheme 6. The thiocarbonylthio group(s) is retained in the polymer which can be reactivated for use as precursors to produce block polymers, star polymers or polymers with more complex architectures [35].…”
Section: Reversible Addition-fragmentation Transfer (Raft) Polymerizamentioning
confidence: 99%
“…SEC analyses showed that the molecular weight increased linearly with conversion, and experimental molecular weights were close to the theoretical values, but the polydispersities (M w /M n = 1.8-1.9) were higher. Save et al [34] first synthesized poly(styrene)-b-poly(4-vinylbenzyl chloride) block co-polymer with S-(benzyldithio) benzoate (BDB) (CTA3) as CTA in bulk. After quaternization of PS-b-PVBC, poly(styrene)-b-poly(vinylbenzyltriethylammonium chloride) PS-b-P(VBTEAC) co-polymer was obtained (Scheme 8).…”
Section: Reversible Addition-fragmentation Transfer (Raft) Polymerizamentioning
confidence: 99%
See 3 more Smart Citations